2012
DOI: 10.1097/paf.0b013e3182662761
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Injuries to Neck Structures in Hanging—An Autopsy Study

Abstract: One hundred eighty-nine cases of known dead bodies brought for medicolegal autopsy with alleged history of hanging were studied at the Department of Forensic Medicine, State Medico Legal Institute, Government Medical College, Thiruvananthapuram, Kerala, India. All the findings noticed during detailed external examination and flap dissection of the neck were analyzed with special emphasis on correlation between the external and internal injuries on neck.There was a preponderance of males in the study group (70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 0 publications
6
41
2
3
Order By: Relevance
“…The hangings in the form that the body does not touch anywhere are called full hanging [1,13,41]. In the literature related to hanging, it is reported that full hanging is most frequently encountered [23,25,30,42]. In the study conducted in Samsun, it was reported that 77.1% of the cases were full hangings [42].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The hangings in the form that the body does not touch anywhere are called full hanging [1,13,41]. In the literature related to hanging, it is reported that full hanging is most frequently encountered [23,25,30,42]. In the study conducted in Samsun, it was reported that 77.1% of the cases were full hangings [42].…”
Section: Discussionmentioning
confidence: 93%
“…Vertebral fractures may occur in primordial executions and at very high distances [1,2,25]. Vertebral fractures may occur in the executions of death penalty and in hangings exercised at very high distances [1,2,25]. Also, in the 2 cases with vertebral fractures mentioned above, the hanging distance were high and both were oldaged.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations